Multiple breath‐hold proton spectroscopy of human liver at 3T: Relaxation times and concentrations of glycogen, choline, and lipids. Issue 2 (17th April 2017) - Weis, Jan; Kullberg, Joel; Ahlström, Håkan
Abstract : Purpose: To evaluate the feasibility of an expiration multiple breath‐hold 1 H‐MRS technique to measure glycogen (Glycg), choline‐containing compounds (CCC), and lipid relaxation times T 1, T 2, and their concentrations in normal human liver. Materials and Methods: Thirty healthy volunteers were recruited. Experiments were performed at 3T. Multiple expiration breath‐hold single‐voxel point‐resolved spectroscopy (PRESS) technique was used for localization. Water‐suppressed spectra were used for the estimation of Glycg, CCC, lipid methylene (CH2 )n relaxation times and concentrations. Residual water lines were removed by the Hankel Lanczos singular value decomposition filter. After phase correction and frequency alignment, spectra were averaged and processed by LCModel. Summed signals of Glycg resonances H2H4′, H3, and H5 between 3.6 and 4 ppm were used to estimate their apparent relaxation times and concentration. Glycg, CCC, and lipid content were estimated from relaxation corrected spectral intensity ratios to unsuppressed water line. Results: Relaxation times were measured for liver Glycg ( T 1, 892 ± 126 msec; T 2, 13 ± 4 msec), CCC ( T 1, 842 ± 75 msec; T 2, 50 ± 5 msec), lipid (CH2 )n ( T 1, 402 ± 19 msec; T 2, 52 ± 3 msec), and water ( T 1, 990 ± 89 msec; T 2, 30 ± 2 msec). Mean CCC and lipid concentrations of healthy liver were 7.8 ± 1.3 mM and 15.8 ± 23.6 mM, respectively. Glycg content was found lower in the morning (48 ± 21 mM) compared to the afternoon (145 ± 50 mM). Conclusion: Multiple breath‐hold 1 H‐MRS together with dedicated postprocessing is a feasible technique for the quantification of liver Glycg, CCC, and lipid relaxation times and concentrations. Level of Evidence: 1 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018;47:410–417.